Madihin of John Tralala and Hendra: A Study of Presentation, Structure, Form, Value, and Function - Rafiek, M. (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
Abstract: This study aims to describe and explain about (1) the structure of the presentation of madihin, (2) the forms of madihin, (3) the values in madihin, and (4) the functions in madihin that were performed by pamadihinan John Tralala and Hendra. This study used Parry and Lord and oral literary approach and it was qualitative research type. The oral literary approach was used to study Madihin's oral literature in terms of presentation structure, form, value, and function. As an oral literature, Madihin can be described qualitatively because the data is submitted verbally by the pamadihinan (someone who presents madihin). After that, the madihin data is discussed in accordance with its presentation structure, form, value, and function. The results of this study are (a) the presentation structure consists of opening, installing tabi, presenting the contents (manguran), and closing; (b) the forms of madihin of John Tralala and Hendra are (1) sampiran, (2) question and answer or question and answer sentence, (3) poem, (4) poem of more than 4 lines and broken rhymes, (5) broken rhyming poem, (6) poem of less than 4 lines, and (7) Answers. So, there are 7 forms of Madihin  of John Tralala and Hendra; (c) the values in madihin of John Tralala and Hendra are (1) the value of loving art, (2) the value of preservation, (3) the value of working together, (4) the value of art appreciation, (5) the value of hard work, (6) the value of honesty, (7) the value of self-confidence or self-flattering, (8) the value of "dropping", (9) the value of reminding (moral), (10) the value of courage to self-defend or not want to lose, (11) the value of self-defending or not willing to budge, and (12) the value of education. So, there are 12 values in Madihin of John Tralala and Hendra; (d) functions in madihin John Tralala and Hendra are functions of education, advice, and entertainment (humor).Key words: presentation, structure, form, value, function, madihin Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan tentang (1) struktur penyajian madihin yang dibawakan oleh pamadihinan John Tralala dan Hendra, (2) bentuk-bentuk madihin yang dibawakan oleh pamadihinan John Tralala dan Hendra, (3) nilai-nilai dalam madihin yang dibawakan oleh pamadihinan John Tralala dan Hendra, dan (4) fungsi-fungsi dalam madihin yang dibawakan oleh pamadihinan John Tralala dan Hendra. Penelitian ini menggunakan pendekatan sastra lisan Parry dan Lord dan berjenis penelitian kualitatif. Pendekatan sastra lisan digunakan untuk mengkaji sastra lisan madihin dari segi struktur penyajian, bentuk, nilai, dan fungsi. Sebagai sebuah sastra lisan, madihin dapat diuraikan secara kualitatif karena data disampaikan oleh pamadihinan secara lisan. Data madihin tersebut kemudian dibahas sesuai dengan struktur penyajian, bentuk, nilai, dan fungsinya. Hasil penelitian ini adalah (a) struktur penyajian  terdiri atas pembukaan, memasang tabi, menyampaikan isi (manguran), dan penutup; (b) bentuk-bentuk madihin John Tralala dan Hendra adalah (1) sampiran, (2) tanya jawab atau kalimat tanya jawab, (3) syair, (4) syair lebih dari 4 larik dan berima patah, (5) syair berima patah, (6) syair kurang dari 4 larik, dan (7) Jawaban. Jadi, ada 7 bentuk madihin John Tralala dan Hendra; (c) nilai-nilai dalam madihin John Tralala dan Hendra adalah (1) nilai cinta seni, (2) nilai pelestarian, (3) nilai bekerja sama, (4) nilai apresiasi seni, (5) nilai kerja keras, (6) nilai keterusterangan, (7) nilai kepercayaan diri atau menyanjung diri, (8) nilai “menjatuhkan”, (9) nilai mengingatkan (moral), (10) nilai keberanian membela diri atau tidak mau kalah, (11) nilai membela diri atau tidak mau mengalah, dan (12) nilai pendidikan. Jadi, ada 12 nilai dalam madihin John Tralala dan Hendra; (d) fungsi-fungsi dalam madihin John Tralala dan Hendra adalah fungsi pendidikan, nasihat, dan hiburan (humor).Kata kunci: struktur penyajian; bentuk; nilai; fungsi; madihin